Λογικὴ λατρεία (Rom 12,1). The Pauline Idea of Worship between the Hebrew and Hellenistic Worlds - Crimella, Matteo (Verbum Vitae, 2021)
This essay focuses on a passage from the Letter to the Romans, better on a famous expression: λογικὴ λατρεία (Rom 12,1). After having studied its context in some depth, it shows how Paul operates in a dual direction: the apostle removes from the expression any kind of semantic link bound up with the cult; he also attributes to it a profane semantic. Paul does not intend to oppose the two cults, Jewish and Christian. His words imply that, like the ancient Israel before them, the Christian believers should also be distinguished for their cult. Christian worship is conceived in a different way. It is far from being a spiritualisation of the cult. Such a reduction is excluded by the object of the sacrifice, «your bodies». Paul operates in two directions: on the one hand, he avoids the trap of supersessionism with regard to the Jewish cult; on the other hand, he excludes a spiritualisation (or interiorisation) of Greek religious practices. Paul’s language is distinct both from the great tradition of Israel and from the Hellenistic world.